Analisis Bentuk Tindak Tutur Direktif dalam Dialog Film “Rembulan Tenggelam di Wajahmu” Karya Tere Liye - Ulin Intan Saputri (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
The purpose of this study is to describe the form of directive speech acts in the dialogue film "Rembulan Drowning in Your Face" by Tere Liye. This research is a descriptive research. The data source of this research is the dialogue film "Rembulan Drowning in Your Face" by Tere Liye. The research data are oral data that contain directive speech acts which include directive speech acts in dialogue. The data was obtained by referring to the method of engaging in engaging free conversation followed by the record, transcript, and note technique. The results of the study of directive speech acts in dialogue had ten data, namely two data forms of command directive speech acts, two data forms of request directive actions. , two solicitation directive speech acts, two advising directive speech acts, and two prohibitive directive speech acts. In conclusion, directive speech acts in film dialogue are divided into five directive speech acts, namely commands, requests, invitations, advice, and prohibitions Keywords: Directives Speech Acts, Dialogue, Film